2015
DOI: 10.7227/cst.10.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Brand Reconciliation? A Case Study of ITV's 2013 Rebrand

Abstract: This article extends existing work in Television Studies on branding through a study of rebranding practices. To this end, the discussion takes the mainstream UK commercial broadcaster ITV's 2013 rebranding as a case study and examines both the institutional contexts motivating change and the construction of its altered brand image through publicity materials. Engaging with the latter allows for strategies of what I have called brand reconciliation as, despite focusing on the channel's contemporary output, pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Andersen et al (2018) raised validity issues from the use of a single case study. In contrast, single interview has been used to advance the understanding of phenomenon such as service quality (Stauss and Weinlich, 1997), as well as corporate rebranding (Garner, 2015). Therefore, this acknowledged potential limitation, with respect to this research, was deemed to be lessened based on the use of multiple interviews and sourcing of secondary company material and organizational insights, from the CEO of O fonds (Stavros and Westberg, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Andersen et al (2018) raised validity issues from the use of a single case study. In contrast, single interview has been used to advance the understanding of phenomenon such as service quality (Stauss and Weinlich, 1997), as well as corporate rebranding (Garner, 2015). Therefore, this acknowledged potential limitation, with respect to this research, was deemed to be lessened based on the use of multiple interviews and sourcing of secondary company material and organizational insights, from the CEO of O fonds (Stavros and Westberg, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…In conclusion, one area where this research does focus on theory lies in providing skepticism of utilizing single case, and single informant studies (Garner, 2015). If this type of case research is muted, within the context of identified research limitations from this study, silenced voices and industry practice will continue to result in a gap in the NPO literature.…”
Section: Conclusion and Future Studymentioning
confidence: 99%
“…It is certainly not my intention here to suggest that EastEnders should somehow be viewed as a lower cultural form given that one actor made a minor mistake during its live performance or that sections of the audience celebrated such an error. Rather, EastEnders ’ celebratory and performed liveness (much like that of Coronation Street as a flagship ITV brand; see Garner, 2015: 13–14) emphasises technical/actorly skill, converting so-called ordinary TV (Bonner, 2003) into extraordinary television drama and sharply challenging the dismissal and denigration of soap which has dogged much of its history (Weissmann, 2016: 367).…”
Section: Commentating and Criticising: Motd’s 50th And Eastenders’ 30mentioning
confidence: 99%